How do banks adjust their capital ratios? Evidence from Germany - Christoph Memmel; Peter Raupach (Deutsche Bundesbank, 2007)
We analyze the dynamics of banks' regulatory capital ratios. Using monthly data of regulatory capital ratios for a subset of large German banks, we estimate the target level and the adjustment speed of the capital ratio for each bank separately. We find evidence that, first, there exists a target level for a substantial percentage of banks; second, that private banks and banks with liquid assets are more likely to adjust their capital ratio tightly; and third, that banks compensate for low target capital ratios with low asset volatilities and high adjustment speeds. Fourth, banks with a target capital ratio seem to use an internal lower limit for their current ratios that is just above the regulatory minimum of 8%.
Keywords: G32; G21; 330; Regulatory bank capital; target capital ratio; partial adjustment; Ornstein-Uhlenbeck process; Bank; Kapitalstruktur; Eigenkapital; Bilanzstrukturmanagement; Schätzung; Deutschland